2020
DOI: 10.12928/telkomnika.v18i5.13840
|View full text |Cite
|
Sign up to set email alerts
|

Pulse shaping methods for inter carrier interference reduction in OFDM system

Abstract: The weakness of the orthogonal freuency division multiplexing (OFDM) system is susceptible to the existence of carrier frequency offset (CFO) which causes the emergence of inter carrier interference (ICI) which causes a degradation of performance OFDM systems. This study aims to apply the suggested rectangular (REC) pulse and improved sinc-power (ISP) pulse shaping methods on OFDM system and determines ICI reduction with the effects of CFO over flat fading Rayleigh channels. The performance of each pulse shapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Research on interference can be done by looking at the performance of the device through the BER meter, eye pattern, and constellation diagram. Wirastuti et al [4], reduction of inter-carrier interference (ICI) is done by simulating the circuit formed by the orthogonal frequency-division multiplexing (OFDM) pulse shaping system. The result of the simulation in terms of BER vs. Eb/No suggested that rectangular (REC) improved sinc-power (ISP) pulse shaping and ISP pulse shaping are more efficient in minimizing intercarrier interference (ICI) no-implemented pulse forming relative to the OFDM system.…”
Section:  Issn: 1693-6930mentioning
confidence: 99%
See 1 more Smart Citation
“…Research on interference can be done by looking at the performance of the device through the BER meter, eye pattern, and constellation diagram. Wirastuti et al [4], reduction of inter-carrier interference (ICI) is done by simulating the circuit formed by the orthogonal frequency-division multiplexing (OFDM) pulse shaping system. The result of the simulation in terms of BER vs. Eb/No suggested that rectangular (REC) improved sinc-power (ISP) pulse shaping and ISP pulse shaping are more efficient in minimizing intercarrier interference (ICI) no-implemented pulse forming relative to the OFDM system.…”
Section:  Issn: 1693-6930mentioning
confidence: 99%
“…It is possible that there is interference from one device to another. For example, wireless fidelity (Wi-Fi) and bluetooth systems can be interferer with a wireless sensor network system, and vice versa [2]- [4]. The problem is how to maintain the presentation of the DQPSK system that gets interference attacks by constructing a better system configuration.…”
Section: Introductionmentioning
confidence: 99%
“…So, in general, OFDM performance is better because pulse formation can reduce the power of the side lobes of subcarriers and potentially cause ICI. Therefore, by using pulse formation, the side lobe subcarrier will not interfere with other subcarriers [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…This technology is remarkably interesting because it can still maintain its performance in poor channel conditions [2], [3]. So, OFDM has been widely used commercially and is still in research development, namely: Digital Video Broadcasting-Terrestrial (DVB-T) [4], Wireless Local Area Network (WLAN) [5], Broadband Wireless Access (BWA) especially IEEE 802.16d WiMAX [6], [7], IEEE 802.20 mobile Broadband Wireless Access (BWA) and Mobile Multimedia Access Communication (MMAC) [8]- [10] as well as 4 th Generation (4G) cellular standards such as Long Term Evolution (LTE) [11]- [14].…”
Section: Introductionmentioning
confidence: 99%